Oral Communication Problems among Neurological Patients in Kelantan: (Masalah Komunikasi Lisan dalam Kalangan Pesakit Neuro di Kelantan) (Jurnal Bahasa, 2018)
This study aims to identify the language problems and difficulties faced by neuro patients during oral communication. It is based on the framework proposed in Lasswell's Communication Model.Purposive sampling technique was used in recruiting participants. The linguistic data were collected based on the interaction between the researcher and 12 neurological patients who were able to participate in a two-way communication using semi-structured questionnaires. The oral interactions were audiotaped and transcribed verbatim and were analysed using thematic analysis. Results show that six out of of 12 patients faced problems and had difficulties in oral communication. Out of the six participants who had communication difficulties, one had problems with fluency, two had problems in language expression, one had problems with articulation and two had problems in explaining the sequence of events. Findings also reveal that there were many factors that contributed to the language and speech difficulties among neurological patients such as disease of the brain, head injuries and abnormalities of speech articulators. These findings are important to provide awareness to patients, families, health professionals and the public about the oral communication problems faced by the neurological patients in order to implement appropriate intervention strategies for them.Keywords: speech, oral communication, communication disorders, neurological patient, aphasia
Keywords: pertuturan; komunikasi lisan; kecacatan komunikasi; pesakit neuro; afasia